Clinical exploration of the international society of limb salvage classification of endoprosthetic failure using Henderson in the application of 3D-printed pelvic tumor prostheses - Liu, Bin; Yang, Fang; Zhang, Tian Wen; Tan, Jiachang; Yuan, Zhenchao (Frontiers in Oncology, 2023)
The use of 3D-printed pelvic prosthesis for postoperative reconstruction after pelvic tumor resection has become one of the primary reconstruction methods; the incidence of complications related to postoperative prosthesis reconstruction is high. Drawing on the failure of the type of bone tumor reconstruction in Henderson, the occurrence of postoperative complications was explored to take advantage of the design improvement of the 3D-printed prosthesis of subsequent pelvic tumors.The data for patients who underwent 3D-printed pelvic tumor prostheses in the Department of Bone and Soft Tissue Surgery at the Affiliated Cancer Hospital of Guangxi Medical University from January 2019 to October 2022 were collected and analyzed.The median follow-up time for all patients was 15.99 months (1.33-31.16 months). At the most recent follow-up, all patients were alive, with an average Musculoskeletal Tumor Society (MSTS) score of 21.46 (17 to 26 points). Local recurrence occurred in two cases 2 (15.3%), metastasis in four cases (30.7%), and complications in 10 cases (76.9%). Early complications after surgery were primarily local wound fissure, deep tissue infection, and postoperative neuralgia. Later complications included loose dissolution of internal fixation, postoperative prosthetic dislocation, and postoperative gluteal middle muscle gait.3D printing personalized design pelvic tumor prosthesis is an effective way to reconstruct, and designing pelvic 3D printed tumor prosthesis with the help of Henderson's bone tumor reconstruction failure concept may help bone tumor surgeons develop better pelvic tumor prosthesis.